Prussian Blue Nanozyme Normalizes Microenvironment to Delay Osteoporosis. Issue 19 (27th July 2022) - Ye, Chenyi; Zhang, Wei; Zhao, Yongzheng; Zhang, Kai; Hou, Weiduo; Chen, Mo; Lu, Jinwei; Wu, Jianrong; He, Rongxin; Gao, Wei; Zheng, Yuanyi; Cai, Xiaojun
Abstract: Osteoporosis (OP) is the most common orthopedic disease in the elderly and the main cause of age‐related mortality and disability. However, no satisfactory intervention is currently available in clinical practice. Thus, an effective therapy to prevent or delay the development of OP should be devised. Osteoclastogenesis overactivation and excessive bone resorption are the main characteristics of OP. Accordingly, a paradigm for nanozyme‐mediated normalization of the disease microenvironment to regulate osteoclast differentiation and delay OP is proposed. Hollow Prussian blue nanozymes (HPBZs) are prepared via template‐free hydrothermal synthesis and selected as representative nanozymes. The intrinsic osteoclast activity‐remodeling bioactivities of the HPBZs are explored in vitro and in vivo, focusing on their impact on osteogenesis and specific molecular mechanisms using an OP murine model. The HPBZs significantly normalize the OP microenvironment, thereby inhibiting osteoclast formation and osteoclast resorption, possibly owing to the suppression of intracellular reactive oxygen species generation, the mitogen‐activated protein kinase, and nuclear factor κ B signaling pathways. Consistently, in an ovariectomy‐induced OP murine model, HPBZ treatment significantly attenuates osteoporotic bone loss in vivo. The findings confirm the HPBZ‐mediated normalization of the disease microenvironment for the treatment of OP and suggest its application to other inflammation‐related diseases. Abstract : The designed hollow Prussian blue nanozymes (HPBZs) significantly normalize the osteoporosis (OP) microenvironment, thereby inhibiting osteoclast formation and osteoclast resorption for treatment of OP, possibly owing to the suppression of the mitogen‐activated protein kinase and nuclear factor κ B signaling pathways. The findings confirm the HPBZ‐mediated normalization of the disease microenvironment for the treatment of OP and even other inflammation‐related diseases.